The impact of information and communication technology on the human development of selected countries - Omar, Dina Ahmed; Dames, Zakaria Hassan Hussein Abu (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this study is to verify the impact of information and communication technology (ICT) on human development in Arab countries (Jordan, Bahrain, Saudi Arabia, Tunisia, the Arab Republic of Egypt and Algeria). In particular, the impact of the Information and Communications Technology Development (IDI) index on the three main components of human development: income, health and education. The study focused on the years (2000-2017) based on the theoretical background shown in the literature, the main study hypothesis was tested using simple linear regression analysis. The results of the study showed different results ranging from positive, negative and insignificant relationship, which reflected the complexity that could be related to the implementation Information and communication technology in the context of development. Arab countries spent a great deal of financial resources to develop the information and communication technology infrastructure, however, they failed to achieve effective use of these technologies in social and economic development. This is due to the incompatibility between the information and communication technology infrastructure, the availability of skilled human capital, the inappropriate education system, and the weekly public awareness of the importance of the role of information and communication technology in social and economic development. Therefore, ICT as a tool alone cannot improve human development unless it occurs in a broader context and a multidimensional strategy that aims to enhance people's capabilities to make the most of these tools and technologies. Finally, the study recommended that GCC policy makers transform their thinking model around information and communications technology by changing their focus from deploying the information and communication technology infrastructure to focus on analyzing and understanding the dynamic complementarities that could shape the potential role of these technologies.